Peningkatan Keterampilan Dalam Menulis Teks Prosedur Melalui Penerapan Model Problem Based Learning (PBL) - Anggy Rukmana Sukram; Muhammad Saleh; St. Suttere (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to improve the skills of writing procedure text through the application of Problem Based Learning (PBL) model in Class XI TKJ 2 SMK Negeri 4 Gowa. The research method used was Classroom Action Research with two cycles. Each cycle consists of planning, implementation, observation, and reflection. The research subjects were 36 students of class XI TKJ 2 SMK Negeri 4 Gowa. Data were collected through written tests on writing procedure texts, observation, and reflection. The data were analysed by using quantitative analysis technique. The results showed that the application of Problem Based Learning (PBL) model could significantly improve the students' procedural text writing skills. In cycle I, the skill of writing procedure text was still in the sufficient category with the percentage of classical completeness of 67.56%. However, in cycle II, there was a significant improvement, with the percentage of classical completeness reaching 91.89%. In addition, observation of learners' participation also showed a significant increase from cycle I to cycle II. The results of this study show that the Problem Based Learning (PBL) model is effective in improving the skill of writing procedure text.